Approach to cartilage lesions and algorithm for treatment [Kikirdak lezyonlarina yaklaşim ve tedavi algoritmasi] - (:unkn) unknown (My University, 2007)
Cartilage symptoms in the knee may be encountered in various forms in orthopedic practice. The first stage from history to treatment is to establish the diagnosis; if the diagnosis is made as a cartilage lesion in the knee, priority must be given to current treatment approaches. The surgeon must provide information regarding etiology, defect thickness, lesion size, the containment of cartilage, localization, stability, meniscal integrity, anatomic alignment of the knee, previous assessments, radiological assessment (direct radiography, magnetic resonance imaging), and general, medical, and systemic conditions, and family history. In this review, a treatment algorithm is presented for the management of articular cartilage lesions.